EFEKTIVITAS PENERAPAN METODE MONTESSORI DALAM UPAYA MEMBANGUN PEMAHAMAN KONSEP DASAR MATEMATIKA SISWA KELAS 1 MI TARBIYATUS SHIBYAN KEMBIRITAN GENTENG BANYUWANGI - Faizah, Kurniyatul; Wiarsih, Nur (International Conference on Humanity Education and Society (ICHES), 2024)
This research aims to determine the effectiveness of implementing the Montessori Method in an effort to build understanding of basic mathematical concepts in grade 1 students at MI Tarbiyatus Shibyan Kembiritan Genteng Banyuwangi. This research is quantitative quasi-experimental, using parallel classes namely classes for the experimental group that receive learning using the Montessori method and control group classes with conventional learning. Data was collected through a test of understanding basic mathematical concepts before (pretest) and after the intervention (post test). The research results show that the average value of N- Gain in the experimental class is 70.00. The average N-Gain value of the control class is 15.47. This shows that the Montessori Method is 54.53% more effective in improving student learning outcomes on adding tens and hundreds than conventional methods. The application of the Montessori method makes a positive contribution to increasing students' understanding, especially in critical aspects of mathematics for grade 1 students. Statistical analysis shows significant differences between the two groups, with a p-value of 0.00<0.05 which supports the effectiveness of the Montessori method. The implication of this research is that the application of the Montessori method can be used as an effective alternative learning approach to build understanding of basic mathematical concepts in grade 1 students. This can be a reference for schools, teachers and policy makers in designing more effective learning strategies at the educational level basic, especially at MI Tarbiyatus Shibyan Kembiritan Genteng Banyuwangi. Further studies can explore the long-term impact of implementing the Montessori method in the context of Islamic education.